2004
DOI: 10.1016/j.jmb.2003.10.042
|View full text |Cite
|
Sign up to set email alerts
|

X-ray Structures of the Maltose–Maltodextrin-binding Protein of the Thermoacidophilic Bacterium Alicyclobacillus acidocaldarius Provide Insight into Acid Stability of Proteins

Abstract: Maltose-binding proteins act as primary receptors in bacterial transport and chemotaxis systems. We report here crystal structures of the thermoacidostable maltose-binding protein from Alicyclobacillus acidocaldarius, and explore its modes of binding to maltose and maltotriose. Further, comparison with the structures of related proteins from Escherichia coli (a mesophile), and two hyperthermophiles (Pyrococcus furiosus and Thermococcus litoralis) allows an investigation of the basis of thermo-and acidostabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 54 publications
3
55
0
Order By: Relevance
“…trehalose/maltose-binding protein and cyclo/maltodextrin-binding proteins) from other sources have also been determined (33,(45)(46)(47) (49), and liganded open (50) states have been reported. In the case of GL-BP, we could not obtain crystals without ligands even after extensive crystallization screening.…”
Section: Analysis Of Ligand Specificity By Itc-mentioning
confidence: 99%
“…trehalose/maltose-binding protein and cyclo/maltodextrin-binding proteins) from other sources have also been determined (33,(45)(46)(47) (49), and liganded open (50) states have been reported. In the case of GL-BP, we could not obtain crystals without ligands even after extensive crystallization screening.…”
Section: Analysis Of Ligand Specificity By Itc-mentioning
confidence: 99%
“…However, since random directed evolution methods require highthroughput screening systems, limitations to improving enzyme properties for many industries still remain (20). As an alternative, three-dimensional (3-D) structure-based rational engineering has been also extensively performed (15,19,34,38). Nonetheless, although recent progress has been made using both methods in engineering enzymes that can operate at a lower pH, attempts to rationally engineer enzymes have been limited to those enzymes whose structures are known (35).…”
mentioning
confidence: 99%
“…To dates, several acidic proteins from Alicyclobacillus acidocaldarius, a thermoacidophilic bacterium that grows optimally at 50 to 60°C and at pH 3 to 4 (7,42), has been investigated for pH-related properties (9,10,33,34,41). For example, although AIs from Bacillus species such as B. subtilis and B. halodurans and from Geobacillus stearothermophilus are highly conserved in terms of amino acid sequences (Ͼ60%), they showed different pH optima (23).…”
mentioning
confidence: 99%
“…3D-RISM-KH calculations were performed in 0.00029 g/cm 3 sodium chloride aqueous solution at temperature 25°C( ≈298 K). The water density was set to 0.99983 g/cm 3 and the dielectric constant to 78.5. The solute−solvent interaction potential comprises the Coulomb and Lennard−Jones interactions.…”
Section: Methodsmentioning
confidence: 99%
“…2,3 The structure of MBP has been resolved in X-ray and NMR spectroscopy experiments both for the liganded (holo) and unliganded (apo) states. 2−12 These studies revealed that MBP has two structural domains connected by the hinge region with the carbohydrate binding site located in the cleft between the domains ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%